Remarks on an Optimal Linear Control Design Applied to a Nonideal and an Ideal Structure Coupled to an Essentially Nonlinear Oscillator - Chavarette, Fábio Roberto; Balthazar, José Manoel [UNESP]; Felix, Jorge L. P. [UNESP] (Asme-amer Soc Mechanical Eng, 2010)
This paper considers a nonlinear dynamics of a particular structure coupled (or uncoupled) to an essentially nonlinear oscillator. We used an optimal linear control design to reduce the amplitude of oscillations and to expand energy consumption, for both ideal and nonideal mathematical models.
Keywords: control system synthesis; linear systems; nonlinear control systems; optimal control; oscillators